Store Brands: Who Buys Them and What Happens to Retail Prices When They Are Introduced? - Bonfrer, Andre (Institutional Knowledge at Singapore Management University, 2004)
In this paper we study store brand demand behavior by examining a panel ofhousehold level and store-level data in five stores located in a competing marketarea. We seek to address three fundamental questions from this data. First, isthere a link between store loyalty and brand loyalty? Second, does store loyaltyraise store brand choice probabilities? Third, if a store brand is introduced intoa category, what happens to the retail prices of the incumbent brands in thecategory? We find that store loyalty is negatively associated with brand loyalty,and that store loyalty increases the likelihood of a store brand purchase in a givencategory. We find mixed evidence on how the retailer changes prices of incumbentbrands when it introduces a store brand to the category. Category level marketstructure measures are used to help identify under what conditions the categoryprices fall or rise. A number of robustness checks are used to help validate ourfindings.